Mitochondrial disease disrupts hepatic allostasis and lowers the threshold for immune-mediated liver toxicity - Maxim Jestin; Senta M. Kapnick; Tatyana N. Tarasenko; Cassidy T. Burke; Patricia M. Zerfas; Francisca Diaz; Hilary Vernon; Larry N. Singh; Ronald J. Sokol; Peter J. McGuire (Elsevier, 2020)
Objective: In individuals with mitochondrial disease, respiratory viral infection can result in metabolic decompensation with mitochondrial hepatopathy. Here, we used a mouse model of liver-specific Complex IV deficiency to study hepatic allostasis during respiratory viral infection. Methods: Mice with hepatic cytochrome c oxidase deficiency (LivCox10−/−) were infected with aerosolized influenza, A/PR/8 (PR8), and euthanized on day five after infection following three days of symptoms. This time course is marked by a peak in inflammatory cytokines and mimics the timing of a common clinical scenario in which caregivers may first attempt to manage the illness at home before seeking medical attention. Metabolic decompensation and mitochondrial hepatopathy in mice were characterized by serum hepatic testing, histology, electron microscopy, biochemistry, metabolomics, and bioenergetic profiling. Results: Following influenza infection, LivCox10−/− mice displayed marked liver disease including hepatitis, enlarged mitochondria with cristae loss, and hepatic steatosis. This pathophysiology was associated with viremia. Primary hepatocytes from LivCox10−/− mice cocultured with WT Kupffer cells in the presence of PR8 showed enhanced lipid accumulation. Treatment of hepatocytes with recombinant TNFα implicated Kupffer cell-derived TNFα as a precipitant of steatosis in LivCox10−/− mice. Eliminating Kupffer cells or blocking TNFα in vivo during influenza infection mitigated the steatosis and mitochondrial morphologic changes. Conclusions: Taken together, our data shift the narrative of metabolic decompensation in mitochondrial hepatopathy beyond the bioenergetic costs of infection to include an underlying susceptibility to immune-mediated damage. Moreover, our work suggests that immune modulation during metabolic decompensation in mitochondrial disease represents a future viable treatment strategy needing further exploration.